Intra-industry trade in the Heckscher-Ohlin-Lerner-Samuelson model - John Somerset Chipman (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1988)
An n-commodity, n-factor, A"-country log-linear model is developed, with identical Cobb-Douglas production coefficients and identical consumer expenditure shares across countries, in which factor endowments are such as to permit positive production of all commodities in all countries, hence equalization of factor rentals among them. Explicit solutions are obtained for the countries' imports, exports, and outputs as well as for equilibrium prices and factor rentals. Allowance is made for interindustrial relationships and trade in intermediate products. Given any set of production and consumption coefficients and any set of world factor endowments which, when suitably allocated among countries, result in positive production of all commodities in all countries, and given any mode of aggregating the n commodities into at most n-1 industrial categories, it is shown that there exists an allocation of the world factor endowments among the K countries such that each country engages in trade and 100% of each country's trade is intra-industry trade (i.e., the values of imports and exports balance each other in each aggregate category).
Keywords: 330; Intraindustrieller Handel; Außenwirtschaftstheorie; Theorie